The banking sector financial restructuring: some evidence for the last decade in the United Kingdom - Σαμίτας, Αριστείδης Γ. (SPOUDAI Journal of Economics and Business, 2004)
This paper uses event study methodology to investigate the banking sector restructuring in United Kingdom. Three large banks have been selected, namely Barclays, Lloyds and National Westminster. The events analysed were changes in group structure, mergers, acquisitions and disposals. The empirical results indicate the impact that these events cause in British banks' stock returns. The effort is to identify and forecast the way that shares prices and generally securities react to market or individual bank's announcements. The study concentrates on the effect that certain unanticipated events have on banks' stock prices. JEL Classification: G21, G34